A new semi-empirical model for estimating the drag coefficient of the vertical random staggered arrays using LES. Issue 180 (September 2018) - Mohammad, Ahmad Faiz; Zaki, Sheikh Ahmad; Ikegaya, Naoki; Hagishima, Aya; Ali, Mohamed Sukri Mat
Abstract: Sheltering of buildings has a significant impact on the total drag of an urban surface. This study performs large eddy simulations (LESs) of flows over vertical random arrays (comprised of buildings with height variability) in staggered layout to estimate the drag coefficient, C D . The vertical random arrays are configured in several frontal area densities, λ F (ratio of buildings' frontal area to total surface area) ranging from 0.09 to 0.81. The sheltering effect is parameterized using the individual building's wind pressure coefficient, C p(t) normalized with that of the isolated building, C p(iso) . The ratio C p(t) / C p(iso) is well correlated with the target building's frontal area density, λ f(t) . Subsequently, the relationship between C p(t) and λ f(t) is expressed using power law equations for three building categories based on the height-to-width ratio, α p ( t ) : tall (2.64 ≤  α p ( t )  ≤ 3.76), medium-rise (1.32 ≤  α p ( t )  ≤ 2.00), and low-rise (0.36 ≤  α p ( t )  ≤ 0.84). Based on the C p(t), an equation of the C D is formulated, yielding the following outcomes. Firstly, the predicted C D values are mostly within 10% of the previous experimental results. Secondly, a semi-empirical model is derived, whereby the predicted C D values are generally consistent for various vertical random arrays. Highlights: Investigations of buildings' sheltering effects on the drag coefficient are lacking. The drag coefficient was determined based on individual buildings' wind pressure coefficients. An equation to estimate the wind pressure coefficient of various buildings was determined. A semi-empirical model of the drag coefficient was formulated. The semi-empirical model was shown to be applicable for various urban arrays.